GENETIC PRIVACY- AN ANALYSIS OF LEGISLATIVE ENDEAVOURS - Singh, Ms Medha; Dubey, Ms. Deepa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Primary evidence is one of the pillars of the Criminal Justice Administration upon which the conviction and acquittal can solely depend. If this primary evidence is in the form of a bodily fluid, hair, fingerprint, nail, saliva etc. it can ascertain the culpability beyond a reasonable doubt. It is pertinent to mention here that our constitution provides a safeguard to the accused in the manner of fundamental rights. This “right” found its nexus in the ever-growing ever-evolving right to life and personal liberty, which very recently was a matter of determination in the Supreme Court by the issue of the right to privacy. The Puttaswamy judgment recognizes multiple facets of the right to privacy and within it the right to preserve “personal information”. It recognizes “personal information” as “data” that should be protected by the State and not misused as means of state surveillance. With this affirmation of data, DNA is genetic data, the Personal Data Protection Bill 2018 and another in 2019, which is the new initiative by State to strengthen the already existing data protection regime. A bare reading of the provisions of this bill can be dubbed as ambiguous and confusing to say the least and recognition to the fact that DNA is “Data” is absent. A careful and thorough reading of the bills is required to further analyze in depth the frontiers of DNA privacy in reference to the stakeholders in the criminal justice system. On the same lines, the Criminal (Procedure) Identification Bill was recently introduced in the lower house all set to repeal the Identification of Prisoners Act 1920. The objective with which this bill is introduced is to quote-unquote expand the definitions of persons whose measurements can be recorded and stored by the law enforcement agencies as admissible evidence and to subsequently arrive to the conclusion of incarceration. The Criminal Procedure (Identification) Bill seeks to achieve high conviction rates as it boastfully states in its draft. This paper shall deal with the critical analysis of the provisions of the DNA Technology (Use and Application) Bill 2019, the Data Protection Bill (pertaining to genetic data only) and the newest edition to this list the Criminal Procedure (Identification) Act 2022.